Fit in a flash [videorecording (DVD)] - Pozo, Cal; Austin, Denise (Lionsgate, 2012)
Get slim in 7. Denise Austin has revved up her workouts to give you a 7-minute solution to ignite your metabolism and start shedding pounds. Delivers seven dynamic workouts focused on cardio, strength training and toning in quick 7-minute intervals.